2019
DOI: 10.1055/s-0038-1677485
|View full text |Cite
|
Sign up to set email alerts
|

Current State of Neuromodulation for Constipation and Fecal Incontinence in Children: A Systematic Review

Abstract: Background Neuromodulation is the application of electrical stimulation on nerve fibers to modulate the neuronal activity. Its use for chronic constipation and fecal incontinence has increased in popularity over the past few years. Invasive and noninvasive techniques are currently available. We reviewed the current literature on the application of the neuromodulation techniques in the management of chronic constipation and fecal incontinence in children. Materials and Methods A search of Healthcare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 40 publications
0
26
0
Order By: Relevance
“…Conclusively, positive influence of interferential electrical stimulation (short-term, medium-to high frequency) on any kind of chronic constipation could be seen (23). Nevertheless, the optimal stimulation parameters have not yet been determined and, while presented results in children are encouraging, multicenter studies are needed to confirm the positive impact on constipation and fecal incontinence (26).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conclusively, positive influence of interferential electrical stimulation (short-term, medium-to high frequency) on any kind of chronic constipation could be seen (23). Nevertheless, the optimal stimulation parameters have not yet been determined and, while presented results in children are encouraging, multicenter studies are needed to confirm the positive impact on constipation and fecal incontinence (26).…”
Section: Discussionmentioning
confidence: 99%
“…However, non-invasive neuromodulation for pediatric patients with chronic constipation has been presented by multiple authors with promising results so far (18)(19)(20)(21)(22)(23)(24). Nevertheless, there are important differences in stimulation variables and outcome of patients.…”
Section: Introductionmentioning
confidence: 99%
“…They also seem to show an improved quality of life for both children and their families. 28 However, these studies found that the evidence was based only on small retrospective samples with a lot of heterogeneity between them with only two randomized controlled trials performed. 29,30 Also the outcomes were reported in many different ways such as, increased of number of bowel movement, decrease of abdominal pain, decrease of episodes of FI, improvement of colonic motility, or decrease of laxative dose.…”
Section: Ileostomymentioning
confidence: 99%
“…In the future, evaluation of other centers' experience, will make it easier to have a better understanding of the results and the outcomes of SNS. 28,31…”
Section: Ileostomymentioning
confidence: 99%
“…Sacral nerve stimulation (SNS) involves low-amplitude electrical stimulation of the sacral nerve via an electrode placed through the sacral foramen [51,52]. In adults, SNS as a treatment option for defecatory symptoms (including constipation) has been under investigation for more than two decades [51].…”
Section: Neuromodulationmentioning
confidence: 99%